Essential-oil pesticidal odorscapes: An exploratory multi-endpoint framework for profiling plant volatiles against walnut-associated stored-product beetles - Gabriel Omar Denett; Maria Rosa Rodriguez; Virginia L. Usseglio; Daniela Milagros Bracamonte; Tamara Elizabeth López; Jose Francisco Aranda Cano; María Paula Zunino; Jorge Omar Werdin Gonzalez; Diego Alejandro Sampietro; Nieves Carolina Comelli (Journal of Stored Products Research, 2027)

Clinical predictors, microbiological profile, and outcomes of bacteremia in patients with cellulitis: a 6-year retrospective cohort study - Ana Cotos Suárez; Amparo López-Bernus; Montserrat Alonso-Sardón; Virginia Velasco Tirado; Laura Sancha Domínguez; Beatriz Rodriguez Alonso; Josue Pendones Ulerio; Juan Luis Muñoz Bellido; Moncef Belhassen-García (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Background Cellulitis is a common cause of hospital admission, yet the clinical relevance and predictors of bacteremia remain incompletely characterized. Identifying patients at risk of bloodstream infection may help optimize diagnostic strategies and clinical management. Methods We conducted a retrospective observational study at a tertiary-care hospital including all consecutive patients hospitalized with cellulitis between January 2019 and December 2024. Patients without blood cultures were excluded. Clinical severity was stratified using the CREST classification. Microbiological data, antibiotic therapy, hospital outcomes, and follow-up at 1 and 3 months were analyzed. Results Among 311 episodes included, bacteremia was confirmed in 46 cases (14.8%). Patients with bacteremia showed significantly higher clinical severity at admission, with CREST grades III–IV present in 56.5% compared with 36.6% in non-bacteremia patients ( p < 0.001). Sepsis occurred in 65.2% of bacteremia cases versus 24.5% of non-bacteremia cases ( p < 0.001). Bacteremia was associated with longer hospital stay (18 ± 18.3 vs 13 ± 9.7 days; p = 0.003) and more frequent antibiotic modifications during admission ( p = 0.023). Streptococcal species and Staphylococcus aureus showed a higher propensity for bloodstream invasion. In-hospital mortality was higher among bacteremia patients (13.0% vs 7.9%), although the difference was not statistically significant. Three-month mortality reached 14.3% in the bacteremia group compared with 9.9% in non-bacteremia patients. Conclusion Bacteremia complicating cellulitis is uncommon but associated with greater clinical severity, longer hospitalization, and increased therapeutic complexity. Severity stratification tools such as CREST may assist in identifying patients at increased risk of bacteremia; however, given their limited discriminatory performance, they should not be used in isolation to guide blood culture collection or other clinical decisions.

Mercury and lead legacy pollution from a coal-fired power plant recorded in lake Chiprana sedimentary record (NE Spain) - Isabel Rodriguez-Veiga; Jorge Pey; Antonio Garralón; Blas L. Valero-Garcés; Thomas Schmid; Alfonso Saiz-Lopez; Connor Doyle; Stefan Schröder; Virginia Peyres; Marcos Mejuto; Miguel Ángel Lominchar; Marcel-Saïd Galofré Penacho; et al. (Journal of Soils and Sediments, 2026)
Purpose The Ebro Basin is one of the most industrialised regions of the Iberian Peninsula, yet its long-term legacy of metal contamination remains poorly constrained due to the scarcity of continuous sedimentary archives in semi-arid environments. This study reconstructs the history of mercury (Hg) and lead (Pb) pollution in the Ebro Basin using Lake Chiprana, the only permanent hypersaline lake providing a continuous, high-resolution sedimentary record in this region. Methods A dated sediment core covering the last ~ 250 years was analysed for Hg and Pb concentrations, enrichment factors, accumulation fluxes and Pb isotopic composition. To link historical contamination with present-day processes, sedimentary data were directly compared with contemporary atmospheric deposition measured by bulk collectors located 5 km from the lake. Geochemical, isotopic and source-apportionment approaches were integrated. Results The sedimentary record shows an increase in Hg and Pb accumulation during the mid-twentieth century, contemporaneous with the operation of a nearby coal-fired power plant. Hg and Pb enrichment factors and accumulation fluxes increased between 1950 and 1980, providing evidence of local coal combustion supported by Pb isotopic signatures. In contrast, recent decades are characterised by lower fluxes and by a clearer expression of mixed sources, including regional dust inputs, Saharan dust, biomass burning, traffic-related emissions and regional dust resuspension. Conclusion The close agreement between recent sedimentary accumulation rates and modern atmospheric fluxes demonstrates the reliability of lake sediments as integrative monitors of pollution legacy in industrialised semi-arid regions. Lake Chiprana emerges as a key reference archive for assessing long-term Hg and Pb contamination and for disentangling historical and contemporary sources affecting soils and sediments in Southern Europe.

In vivo biocompatibility of poly-N-isopropylacrylamide (PNIPAM) hydrogels in Wistar rats: Hematological, biochemical, and histopathological assessments - Rocío Bonino; Andrés Sommaro; Virginia Capella; Matías Caverzan; Bianca Opizzo; Lázaro Zabaldano; Nancy Rodriguez; Pablo Bosch; Claudia Rivarola; Ana Cecilia Liaudat (Tissue and Cell, 2026)

In silico and experimental characterization of fipronil–membrane interactions: Implications for pesticide selectivity - Marcos A. Asis-Rodriguez; Mariela E. Sánchez-Borzone; Daniel A. García; Virginia Miguel (Pesticide Biochemistry and Physiology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The Effect Of Localized Circumferential Residual Stress On Pressurized Stress State Of CT Reconstructed Vessels: A Finite Element Study - Vittorio Lissoni; Martina Schembri; Giulia Luraghi; Alessandro Caimi; Virginia Fregona; Mauro Di Giancamillo; Jessica Bassi; Ferdinando Auricchio; Michele Conti; Gabriele Dubini; Francesco Migliavacca; Jose Felix Rodriguez Matas (Annals of Biomedical Engineering, 2026)
Purpose Residual stresses are intrinsic stresses present in arteries even in the absence of external loads or blood pressure. They originate during growth and remodeling and contribute to vascular mechanical equilibrium. Despite advances in computational methods, incorporating residual stresses into patient-specific vascular models remains challenging. Evidence regarding the influence of circumferential residual stresses on physiological loading in realistic anatomies is still limited. Methods We combined in vitro imaging, mechanical testing, and finite element (FE) simulations to incorporate residual stresses into a pressurized porcine aorta model. Medical images were acquired in both pressurized and zero-stress states, the latter obtained after 2 h of longitudinal cutting. Locally measured mechanical properties from distinct aortic regions were used to define an orthotropic hyperelastic material response. Residual stresses were restored by simulating vessel closure under displacement-controlled boundary conditions with a tied contact interface. Stress distributions were then compared in FE pressurization simulations performed with and without residual stresses. Results Residual stresses substantially influenced the predicted stress fields. They homogenized stress across the vessel thickness and reduced stress concentrations near the lumen. Moreover, lumen cross-sectional areas at 120 mmHg aligned more closely with experimental measurements when residual stresses were included. In contrast, neglecting residual stresses produced an average overestimation of lumen area by 4.84% and stress peaks up to 50% higher in the inner wall. Conclusion This study highlights the importance of accounting for residual stresses in biomechanical vascular simulations. Incorporating them improves prediction accuracy and reduces artificial stress concentrations, which is crucial for patient-specific risk assessment and surgical planning.

Clinical image analysis to build patient-specific models of acute ischemic stroke patients - Virginia Fregona; Ilaria Bottini; Sara Barati; Amedeo Cervo; Antonio Macera; Ghil Schwarz; Guglielmo Pero; Mariangela Piano; Gabriele Dubini; Jose Felix Rodriguez Matas; Giulia Luraghi; Francesco Migliavacca (Physical and Engineering Sciences in Medicine, 2026)
Mechanical thrombectomy (MT) is an emergency treatment for acute ischemic stroke (AIS) to remove a clot occluding a large cerebral vessel. Histological analysis on retrieved thrombi have shown that they are mainly composed of red blood cells (RBCs), platelets and fibrin, and the outcome of MT appears to be influenced by clot composition. Therefore, being able to predict clot composition from routine medical images used for AIS diagnosis could support the choice of interventional strategy. Along with that, finite element simulations of the MT procedure can help provide insights into the impact of the procedural choices, the vessels morphology and the clot characteristics on the MT outcome. To achieve this, a realistic representation of the involved structures is necessary. In this context, this work aimed to (i) develop a methodology for the analysis of routine radiological images aiming at inferring information about clot characteristics (position, length, and composition) and (ii) develop a semi-automatic pipeline to position the clot in the patient-specific reconstructed geometry to build a patient-specific model which could be the starting point for the in silico replica of the MT procedure. However, image analysis alone could not distinguish between white and mixed clots, while a distinction between red and non-red clots was possible. Consequently, histological analyses were used to assign the clot composition, and thus the mechanical properties, in the positioning simulation. The resulting patient-specific model showed a strong similarity with pre-interventional clinical images.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Effect of Probiotics on Sperm Quality in the Adult Mouse - Ana Sanchez-Rodriguez; Ingrid I. D. Idrovo; Rocío Villafranca; Nerea Latorre; Juan Antonio Rielo; Ane Laburu; Sandra Nieto-Román; Daniel Heredia; Rubén González; Virginia García-Cañas; Diego Laxalde; Carolina Simó; et al. (Probiotics and Antimicrobial Proteins, 2025)
The administration of probiotics for the treatment of different diseases has gained interest in recent years. However, few studies have evaluated their effects on reproductive traits. The objective of this study was to examine the effect of two mixtures of probiotics, a commercial probiotic (Vivomixx®) and a mix of Lacticaseibacillus rhamnosus GG and Faecalibacterium duncaniae A2-165, on sperm quality in a mouse model. Adult male mice (8 months old) were used for two experimental and one control groups ( n = 5 each). The probiotics or physiological serum (control) was administered orally, twice a week, during 5 weeks. Sperm were collected from the cauda epididymis, and their total number, motility, kinematics, morphology, and acrosome integrity were assessed in recently collected samples and after a 60-min in vitro incubation. Results showed a higher percentage of normal sperm in both experimental groups, with fewer head abnormalities than in the control. Differences were found among groups in the morphometry of sperm heads, being more elongated in mice treated with probiotics. Sperm from probiotic-treated mice showed similar total motility when compared to the controls, although the proportion of progressively moving sperm and their vigor of motility were lower. Sperm swimming descriptors were measured with a CASA system. Velocity parameters were similar among groups whereas linearity was higher in mice treated with the commercial probiotic. These results suggest that the administration of probiotics may increase the proportion of sperm with normal morphology and lead to modifications in sperm head shape that may enhance sperm swimming. Studies using a longer administration period would be useful in further characterizing the effect of these probiotic mixtures on sperm quality and fertilization capacity.

Cell biology features and gene expression programs modulating cell expansion during root organ growth - Camila Goldy; Virginia Barrera; Mariana Sotelo-Silveira; Ramiro E. Rodriguez (Current Opinion in Plant Biology, 2025)

Flexible feeding strategy for high-yield PHA bioprocessing in Cupriavidus necator H16 from anaerobically fermented industrial wastewater - Natalia Hernández-Herreros; Alberto Rodriguez; Virginia Rivero-Buceta; Antonia Rojas; M. Auxiliadora Prieto (Bioresource Technology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Fosfomycin in bacteraemic urinary tract infection due to multidrug-resistant Escherichia coli : insights of post hoc DOOR analysis of the FOREST trial - Jesús Sojo-Dorado; Inmaculada López-Hernández; Belén Gutiérrez-Gutiérrez; Sandra De la Rosa-Riestra; Fernando Docobo-Pérez; Alicia Hernánez-Torres; Álvaro Pascual; Jesús Rodriguez-Baño; Esperanza Merino de Lucas; Laura Escolà-Vergé; Elena Bereciartua; Elisa García-Vázquez; et al. (Infectious Diseases, 2025)

Crustal mobility analysis in the proximal Andean broken foreland at 31°S: A geodetic and geophysical approach - Flavia Leiva; Francisco Ruiz; Aixa Rodriguez; Gemma Acosta; Marcelo Gonzalez; Franco Clavel; Guido M. Gianni; Virginia Mackern; Federico Lince Klinger; Héctor P.A. Garcia; Marianela Lupari; Marcos Sánchez; et al. (Journal of South American Earth Sciences, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Biosurfactant production by Rhodococcus ALDO1 isolated from olive mill wastes - Paola Sanmartin Negrete; Carolina Ghilardi; Lina Rodriguez Pineda; Ethel Pérez; Maria Lidia Herrera; Virginia Borroni (Biocatalysis and Agricultural Biotechnology, 2024)

Nanoscale calcium uranyl carbonate clusters in water - Samuel N. Perry; Virginia G. Rodriguez; Peter C. Burns (Chemical Geology, 2023)

Kinetics of Na- and K- uranyl arsenate dissolution - Isabel Meza; Noah Jemison; Jorge Gonzalez-Estrella; Peter C. Burns; Virginia Rodriguez; Ginger E. Sigmon; Jennifer E.S. Szymanowski; Abdul-Mehdi S. Ali; Kaelin Gagnon; José M. Cerrato; Peter Lichtner (Chemical Geology, 2023)

Eucalyptus bleached kraft pulp-ionic liquid inks for 3D printing of ionogels and hydrogels - Cynthia Hopson; Victoria Rigual; M. Virginia Alonso; Mercedes Oliet; Francisco Rodriguez (Carbohydrate Polymers, 2023)

Protein recovery from brewery solid wastes - Luciana M. Rodriguez; Julia L. Camina; Virginia Borroni; Ethel E. Pérez (Food Chemistry, 2023)

Enacting boundaries or building bridges? Language and engagement in food-energy-water systems science - Valoree S. Gagnon; Chelsea Schelly; William Lytle; Andrew Kliskey; Virginia H. Dale; Anna-Maria Marshall; Luis F. Rodriguez; Paula Williams; Michael Waasegiizhig Price; Elizabeth A. Redd; Margaret A. Noodin (Socio-Ecological Practice Research, 2022)
Scientific study of issues at the nexus of food–energy–water systems (FEWS) requires grappling with multifaceted, “wicked” problems. FEWS involve interactions occurring directly and indirectly across complex and overlapping spatial and temporal scales; they are also imbued with diverse and sometimes conflicting meanings for the human and more-than-human beings that live within them. In this paper, we consider the role of language in the dynamics of boundary work, recognizing that the language often used in stakeholder and community engagement intended to address FEWS science and decision-making constructs boundaries and limits diverse and inclusive participation. In contrast, some language systems provide opportunities to build bridges rather than boundaries in engagement. Based on our experiences with engagement in FEWS science and with Indigenous knowledges and languages, we consider examples of the role of language in reflecting worldviews, values, practices, and interactions in FEWS science and engagement. We particularly focus on Indigenous knowledges from Anishinaabe and the language of Anishinaabemowin, contrasting languages of boundaries and bridges through concrete examples. These examples are used to unpack the argument of this work, which is that scientific research aiming to engage FEWS issues in working landscapes requires grappling with embedded, practical understandings. This perspective demonstrates the importance of grappling with the role of language in creating boundaries or bridges, while recognizing that training in engagement may not critically reflect on the role of language in limiting diversity and inclusivity in engagement efforts. Leaving this reflexive consideration of language unexamined may unknowingly perpetuate boundaries rather than building bridges, thus limiting the effectiveness of engagement that is intended to address wicked problems in working landscapes.

Toad invasion of Malagasy forests triggers severe mortality of a predatory snake - Fulvio Licata; Rodino Fetraharijaona Harison; Gentile Francesco Ficetola; Karen Freeman; Benjamin J. Muller; Virginia Rodriguez Ponga; Franco Andreone; Angelica Crottini (Biological Invasions, 2022)

Influence of the time of fungicide application in the production of trichothecenes on field inoculated spikes from wheat grown in Argentina - Natalia Pesquero; Diana Ramirez Albuquerque; Dante Rojas; Enrique Alberione; Anabel Rodriguez; Ricardo Moschini; Virginia Fernandez Pinto (Australasian Plant Pathology, 2021)

Reduction of Ethanol Yield from Switchgrass Infected with Rust Caused by Puccinia emaculata - Virginia R. Sykes; Fred L. Allen; Jonathan R. Mielenz; C. Neal Stewart; Mark T. Windham; Choo Y. Hamilton; Miguel Rodriguez; Kelsey L. Yee (BioEnergy Research, 2016)

Understanding the Role of the Biological Pump in the Global Carbon Cycle: An Imperative for Ocean Science - Susumu Honjo; Timothy Eglinton; Craig Taylor; Kevin Ulmer; Stefan Sievert; Astrid Bracher; Christopher German; Virginia Edgcomb; Roger Francois; M. Debora Iglesias-Rodriguez; Benjamin Van Mooy; Daniel Rapeta (Oceanography, 2014)

A regulated deficit irrigation strategy for hedgerow olive orchards with high plant density - José E. Fernández; Alfonso Perez-Martin; José M. Torres-Ruiz; María V. Cuevas; Celia M. Rodriguez-Dominguez; Sheren Elsayed-Farag; Ana Morales-Sillero; José M. García; Virginia Hernandez-Santana; Antonio Diaz-Espejo (Plant and Soil, 2013)

A comparison among different modified Priestley and Taylor equations to calculate actual evapotranspiration with MODIS data - Virginia Venturini; Leticia Rodriguez; Gutam Bisht (International Journal of Remote Sensing, 2011)

Temporal and spatial infection dynamics indicate recognition events in the early hours of a dinoflagellate/coral symbiosis - Mauricio Rodriguez-Lanetty; Elisha M. Wood-Charlson; Lea L. Hollingsworth; Dave A. Krupp; Virginia M. Weis (Marine Biology, 2006)